Penggunaan Metode Problem Based Learning dalam meningkatkan keaktifan belajar siswa pada kelas XI IPS 1 - Iwan Ramadhan (Cetta: Jurnal Ilmu Pendidikan, 2021)
The learning process has the use of various learning methods, one of which is the Problem Based Learning (PBL) method. The research problem is how the planning steps and the process of implementing the PBL method in increasing student learning activity in class XI IPS 1 at SMA Mujahidin Pontianak. The purpose of this study was to obtain information and clarity regarding the planning steps and the process of applying the PBL method as well as student learning acquisition in increasing student learning activity in class XI IPS 1 at SMA Mujahidin Pontianak. The research method used is a qualitative approach method. Active learning in class XI students at SMA Mujahidin Pontianak includes three domains, namely; Cognitive skills, namely initiative, activeness, cooperation, and accuracy in answering students have scores above the PP-completeness of 83%. Affective; acceptance, participation, assessment/determination of character, and organization whose percentage is above 83.33% completeness. Psychomotor; children's movements include perception, readiness, guided movements and complex movements based on observations showed that, children followed well by 78.34%.